Strengthening the Role of Local Institutions in Protecting the Environment of ??Mount Lawu Areas for Tourism Purposes - Sari, Suzanna Ratih; Sutirto, Tunjung Wahadi; Sugiarti, Rara (Komunitas, 2017)
Strengthening the role of local institutions in protecting the environment of Mount Lawu areas is become an important thing that has to do by local government together with local people, especially to increase the value of local resources for tourism purposes. This suitable to encourage young generation to protect and manage their environment so that the function of the environment can be sustained and promoted to tourists. Presently, many local people are not aware of their enviroment. Many activities tend to destruct and exploit the environment. If such condition is being allowed, then, tourists and young generation will not have a chance to enjoy and experiance the beauty of the environment. Based on the above statement, this study is done to explore in detail how local people in Mt. Lawu through their local organization tried to protect their very useful and worthfull environment and promote it as tourism assets.